Factors of future teachers’ motivation formation for the physical improvement - Hakman, Anna; ANDRIEIEVA, OLENA; KASHUBA, VITALII; BEZVERKHNIA, HALYNA; TSYBULSKA, VIKTORIA; MAIEVSKYI, MYKOLA; OSADCHENKO, TETIANA; SEMENOV, ANDRII; KLJUS, OLENA; TSIUNIAK, OKSANA; NIKULA, NATALIIA; TOMENKO, OLEKSANDR (Baltic Journal of Health and Physical Activity, 2021)
Background: The article uses factor analysis to obtain an insight into the peculiarities of the motivation for physical improvement of students from the Faculty of Primary Education with different modes of attendance. Material and methods: Analysis and synthesis of references, surveying, psychological testing, pedagogical experiment, and methods of mathematical statistics were applied. The study involved 173 female students (18–22 years of age) of pedagogical profile with full- and part-time attendance. Results: The survey highlighted the motivational factors that affect the involvement of female students of pedagogical profile in physical improvement. The motivational factors for second- and fourth-year female students with full- and part-time attendance were emphasized separately. Based on the aforementioned data, factor analysis was conducted involving the abovementioned indicators. Conclusions: The data of the conducted study on the involvement of female students from the Faculty of Primary Education indicate that second- and fourth-year full-time female students have the motivation for “acquiring knowledge” and that for “mastering a profession”. By contrast, second- and fourth-year part-time female students demonstrate the motivation for “mastering a profession”. For fourth-year full-time female students, the difference in the motivations for “acquiring knowledge” and “mastering a profession”.
Keywords: motivation, future teachers, factors, physical improvement